Unscrambling Chaos through Thick and Thin - Melese, Francois; Transue, William (Quarterly Journal of Economics, 1986)
Francois Melese, William Transue; Unscrambling Chaos Through Thick and Thin, The Quarterly Journal of Economics, Volume 101, Issue 2, 1 May 1986, Pages 419